Bending collapse of closed-hat-section beams. Part I: Development and validation of finite element models / Hafizan Hashim...[et al.] - Hashim, Hafizan; Ab.Ghani, Amir Radzi; Kuntjoro, Wahyu (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Many articles on bending collapse but not limited to closed-hat-section have been reported mainly from experimental point of view but less in simulation-based approach. This paper presents the procedure for development and validation of a finite element (FE) model of a closed-hat-section beam under quasi-static three-point bending using an explicit non-linear FE technique. Developed FE models were validated through comparison with existing and present experiment results. Firstly, the existing models were rebulit via present modelling technique using information provided in the relevant research report. Simulation results of rebuilt model were compared with existing results for verification and validation. Next, to further validate the present model, actual physical experiment replicating the FE model was set up for comparison of results. Overall, both group of comparison results emphasis force, mean load-displacement relationship, and deformation modes show good agreement. Adequate robustness and stability of the present model were achieved when responses from different material and cross section were well predicted.